Analysis of the low functional allele 7(TA) of the UGT1A1 gene in healthy population in the Western region of Ukraine - HaiboniukІ.; Makukh, H. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
Gilbert’s syndrome, GS (non-hemolytic anemia) is a pathological condition caused by enzyme (uridine diphosphate glucuronosyltransferase) failure to degrade bilirubin because of UGT1A1 gene mutations, which generally are TA insertions in the promoter region. Disorder entails constantly high level of bilirubin in the blood, and its toxicity causes symptoms manifestation. The pathology doesn’t require therapy, but it increases the risk of concomitant disorders and requires a special approach when prescribing therapy with drugs. The frequency of Gilbert’s syndrome ranges from 0.6% to 43% worldwide, the frequency in Ukraine is not known exactly. Thus, the aim of the work was, based on analysis of published data, to study the world distribution of Gilbert’s syndrome risk alleles, to find their associations with other pathological conditions, and to establish the frequency of the low-functional allele and various genotypes in TA [A(TA)6TAA] locus of UGT1A1 gene among residents of the Western region of Ukraine. Blood samples from 130 healthy residents of the Western region of Ukraine were collected, DNA samples were isolated by salting method. DNA amplification was performed by PCR followed by 10% PAG analysis and HRM analysis (high resolution melting). The pathogenic allele frequency was 34.3%, the frequency of the ancestral allele was 65.7%. The frequency of the mutant homozygous genotype was 14.6%, which coincides with published data. The frequency of the mutant genotype equals 8–18% for European countries, so our data coincide with results of population studies of European countries residents. It should be noted that these 14.6% of population are of high risk of concomitant disorders, such as colorectal cancer in men, breast cancer in women, diseases of the gastrointestinal tract, biliary calculus and formation of kidney stones. Thus, it is advisable to analyze 7(TA) alleles (risk alleles for Gilbert’s syndrome) of the UGT1A1 gene in patients with hyperbilirubinemia of undetermined origin to diagnose Gilbert’s syndrome.